The Dissemination Model of Cultural Information Using Instagram - Walda Khoiriyah; Elya Riska Dwi Wahyuni; Nindya Indrasweri (Program Studi Ilmu Perpustakaan UIN Alauddin, 2021)
Instagram is one of the social media that is used massively to disseminate information, particularly regarding cultural information. This paper describes a model for disseminating cultural information using social media Instagram. The research was conducted at the Paniradya Kaistimewan of DIY. The data were collected through three techniques, namely participatory observation, interviews, and literature study. Participation observations were carried out by the first author through internship program for three months in 2020 and actively participated in document management activities as well as disseminating management results in the form of information through Instagram. The result of this research is the cultural information dissemination model used by Paniradya Kaistimewan Yogyakarta of DIY with transmissional communication formula model. The conclusion of the research is that dissemination through Paniradya Kaistimewan of DIY's Instagram can increase the brand trust of Paniradya Kaistimewan DIY. This is proven by public opinion that Paniradya Kaistimewan of DIY is a source of public reference for the privileged values of DIY.